Effect of alloying on transformation temperatures and magnetoplasticity in Ni-Mn-Ga alloys - Glavatska, N.; Dobrinskiy, A.; Glavatskiy, I.; Urubkov, I.; Ge, Y.; Soderberg, O.; Hannula, S.-P. (Functional Materials, 2006)
In this work, the alloying effect ternary Ni-Mn-Ga alloys on the phase transformation temperatures and magnetoplasticity potential has been investigated. Several ternary and quaternary off-stoichiometric compositions of Ni-Mn-Ga alloys and Ni-Mn-Ga-X ones (where X = Si, in, Co, Fe) have been studied. The phase transformation temperatures were В работе исследовано влияние легирования на температуры фазовых превращений и способность к магнитопластичноети сплавов Ni-Mn-Ga. Исследовано несколько композиций нестехиометрических сплавов Ni-Mn-Ga и Ni-Mn-Ga-X (где X = Si, in, Co, Fe). В роботі досліджено вилив легування на температури фазових перетворень та здатність до магнітопластичності сплавів Ni-Mn-Ga. Досліджено декілька композицій нестехіометричніх сплавів Ni-Mn-Ga та Ni-Mn-Ga-X (де X = Si, in, Co, Fe).